PROJECT-BASED LEARNING APPROACH APPLIED IN THE COURSE "CODING IN TELECOMMUNICATION SYSTEMS" - Borodzhieva, Adriana (The International Scientific Conference eLearning and Software for Education, 2021)
The paper describes the application of the project-based learning approach for increasing students' motivation for studying in the course "Coding in Telecommunication Systems" on the topic of Hamming codes by using different computer-based tools such as MS Excel, Logisim, etc. The applications are used in the educational process in the course "Coding in Telecommunication Systems" for Bachelors in the specialty "Internet and Mobile Communications" in our University.